PERAN LAYANAN BIMBINGAN KONSELING DALAM PENGEMBANGAN KARAKTER SISWA - Kholila Rachmadiyanti (STKIP PGRI SUMENEP, 2024)
Counseling guidance services are not just providing advice related to choosing majors, careers or solving behavioral problems, but are an effective forum in shaping student character. Counseling guidance becomes another way for children's character building besides parents and the environment. character development is a lifelong process, which aims to form individuals who have noble values, morals, and ethics. The purpose of making this article is to find out the role of counseling guidance services on student character development. The method used in this article uses the literature review method by analyzing several studies related to the discussion. The results show that the role of counseling guidance on student character development is very instrumental, through various ways, one of which is a routine event that is held indirectly will develop student character for the better.